2002
DOI: 10.1016/s1074-7613(02)00446-6
|View full text |Cite
|
Sign up to set email alerts
|

SOCS1/JAB Is a Negative Regulator of LPS-Induced Macrophage Activation

Abstract: Bacterial lipopolysaccharide (LPS) triggers innate immune responses through Toll-like receptor (TLR) 4. We show here that the suppressor of cytokine-signaling-1 (SOCS1/JAB) is rapidly induced by LPS and negatively regulates LPS signaling. SOCS1(+/-) mice or SOCS1(-/-) mice with interferon-gamma (IFNgamma)-deficient background were more sensitive to LPS-induced lethal effects than were wild-type littermates. LPS-induced NO(2)(-) synthesis and TNFalpha production were augmented in SOCS1(-/-) macrophages. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
496
1
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 595 publications
(521 citation statements)
references
References 50 publications
17
496
1
7
Order By: Relevance
“…LPS-induced IκB and p38 phosphorylation was up-regulated in SOCS1 -/-macrophages and forced expression of SOCS1 suppressed LPS-induced NF-κB activation (18). Since the expressions of proinflammatory mediators and the activity of NF-κB are known to be modulated by SOCS1, we found that albaconol could induce SOCS1 up-regulation in RAW264.7 cells stimulated by LPS, thus outlining one of mechanistic explanation for the antiinflammatory effect of albaconol.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…LPS-induced IκB and p38 phosphorylation was up-regulated in SOCS1 -/-macrophages and forced expression of SOCS1 suppressed LPS-induced NF-κB activation (18). Since the expressions of proinflammatory mediators and the activity of NF-κB are known to be modulated by SOCS1, we found that albaconol could induce SOCS1 up-regulation in RAW264.7 cells stimulated by LPS, thus outlining one of mechanistic explanation for the antiinflammatory effect of albaconol.…”
Section: Discussionmentioning
confidence: 50%
“…Recently, SOCS1 was found to be induced by LPS stimulation in macrophages (16) and it is reported that SOCS1 is an essential down-regulating factor for protecting host from fatal responses to LPS (17). Particularly, SOCS1 overexpression suppressed LPS-induced IκB phosphorylation and NF-κB transcriptional activity (18). Therefore, to determine if albaconol could induce SOCS1 expression to suppress LPS signaling, we analyzed LPS-induced expression of SOCS1 in RAW264.7 cells pretreated with albaconol.…”
Section: Albaconol Up-regulates Lps-induced Socs1 Expression In Macromentioning
confidence: 99%
“…Whereas SOCS-1 functions by binding directly to JAK proteins, SOCS-3 binds to phosphorylated tyrosine on the receptor. SOCS-1 and SOCS-3 are also induced by JAK/STAT-independent stimuli, such as LPS, CpG, TNF␣, and insulin (36,37). Indeed, we demonstrated that costimulation with either LPS or TNF␣ enhanced SOCS-1 and SOCS-3 mRNA expression.…”
Section: Discussionmentioning
confidence: 56%
“…Interestingly, SIGIRR is also highly expressed in epithelial cells, suggesting that it too may suppress signaling at sites of constitutive microbial exposure. Finally, suppressor of cytokine signaling-1 (SOCS-1) has been reported to negatively regulate LPS signaling to NF-kB and socs1 À/À mice exhibit an inflammatory phenotype that is consistent with this prediction (Kinjyo et al, 2002;Nakagawa et al, 2002). SOCS-1 may function by directly targeting TIRAP/Mal, and selectively inhibit TLR4 signaling through the TIRAP/Mal/MyD88 pathway (Mansell et al, 2006).…”
Section: Toll-like Receptorsmentioning
confidence: 73%